Antibacterial and anti-inflammatory properties of Synadenium umbellatum in vitro - Ramos, A. P.S.; Gaban, L.; Oliveira, S. H.P. [UNESP]; Ramos, C. D.L. (International Society for Horticultural Science (ISHS), 2018)
The species Synadenuium umbellatum belongs to the Euphorbiaceae family and is widely found in South America and popularly known in Brazil as “cola-nota”, “avelós”, “cancerola” or “milagrosa”. The latex collected from this plant is empirically used as an aqueous solution for treatment of several purposes including anti-inflammatory and antimicrobial properties. The objective of this study was to investigate the effect of the crude latex in the bacterial culture and in the phagocytic properties of macrophages against yeast Saccharomyces cerevisiae. To evaluate the antimicrobial activity, we tested the effect of crude latex from S. umbellatum against four bacterial strains: Staphylococcus aureus, Escherichia coli, Pseudomonas aeruginosa and Klebsiella pneumoniae. Cytotoxicity assay was performed in peritoneal macrophages by MTT reduction assay. Phagocytic assay was undertaken in macrophages incubated with yeast and latex. After incubation period, the cells were stained and the yeast forms from S. cerevisiae inside macrophages were counted, and the phagocytic index (PI) determined. The results demonstrated that the crude latex was not effective against the bacterial strain tested. When the latex was tested in murine peritoneal macrophages, we observed a time and concentration-dependent cytotoxicity when compared with control. To test the activity to the latex in phagocytosis, we used the concentrations that did not induce toxicity in the macrophages. Interestingly, we observed an improved phagocytic capacity in the cells incubated with three latex titration (LT) (Control, PI=4.9±0,23; LT1:30, PI=9.8±3; LT1:60, LTPI=9.5±3; LT1:120, PI=22.3±1,0; n=4). The results showed that S. umbellatum presents a concentration-dependent cytotoxicity and promotes an improved phagocytic capacity in macrophages. Despite the latex not presenting a direct antibacterial activity against bacterial strains tested, the results suggest that components present in the latex could trigger an improved inflammatory response against infection agents by stimulating the macrophages phagocytic properties.
Keywords: Antibacterial; Cytotoxicity; Inflammation; Macrophages; Phagocytosis; Synadenium umbellatum